Tetrio Sphinx, Giant Gray Sphinx, Frangipani Hornworm, Pseudosphinx tetrio (Linnaeus) (Insecta: Lepidoptera: Sphingidae) - James C. Dunford; Kathryn A. Barbara (EDIS)
The tetrio sphinx, Pseudosphinx tetrio (Linnaeus), is a common moth in the American tropics and subtropics that less frequently occurs in southern parts of Florida. Although the adults exhibit mostly drab grey coloration, larvae are conspicuous, large caterpillars that often occur in gardens feeding on frangipani and other members of the dogbane family (Apocynaceae). This document is EENY-344, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2005.